2024
DOI: 10.3389/fncel.2024.1371587
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and turnover disruption of olfactory sensory neurons in eosinophilic chronic rhinosinusitis

Yuetong Chen,
Minghan Li,
Juan Lu

Abstract: Olfactory dysfunction (OD) is one of the important and difficult-to-treat symptoms of eosinophilic chronic rhinosinusitis (CRS), which is typically associated with type 2 inflammation where eosinophils (EOSs) function as both effectors and initiators. Eosinophilic infiltration in the olfactory mucosa (OM) is associated with severe OD, mucosal erosion, and more loss of olfactory sensory neurons (OSNs). Active EOS-derived cytokines, chemokines, and eosinophil granule proteins may lead to aggravation of inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…Much like vision and hearing, the faculty of smell invariably declines with age [52], attributable to factors such as decreased regenerative capacity [53], cellular apoptosis [54], and disruptions in neural transmission [55]. Different from normal age-related olfactory decline, the above process is further exacerbated in PD patients due to neurodegenerative or other PD-related pathological lesions [16].…”
Section: Discussionmentioning
confidence: 99%
“…Much like vision and hearing, the faculty of smell invariably declines with age [52], attributable to factors such as decreased regenerative capacity [53], cellular apoptosis [54], and disruptions in neural transmission [55]. Different from normal age-related olfactory decline, the above process is further exacerbated in PD patients due to neurodegenerative or other PD-related pathological lesions [16].…”
Section: Discussionmentioning
confidence: 99%
“…After transsphenoidal surgery, the olfactory epithelium and its surrounding mucosa may experience issues such as blood scab formation and structural changes ( 27 ), leading to physical blockage of airflow in the nasal cavity, preventing odor molecules from reaching the olfactory receptor neurons and impacting the recovery of olfactory function. Furthermore, eosinophilic infiltration may occur in the area of blood crust formation, resulting in prolonged exposure of the nasal mucosa to fungal extracts, leading to significant thinning of the olfactory epithelium and exacerbating the development of olfactory dysfunction ( 26 , 28 , 29 ). Koskinen et al ( 30 ) also found that the long-standing nasal blood scab may lead to chronic bacterial colonization, and further affecting the olfactory function.…”
Section: Discussionmentioning
confidence: 99%